Implementation of the Echo Hiding Steganography Method for Embedding Secret Messages in Audio Media - Kevin Marcho Nainggolan; Kasih Delayana Marpaung; Wetina Hulu (BIOS: Jurnal Informatika dan Sains, 2026)
The development of digital technology and audio communication has increased the intensity of information exchange through online media, but it also raises the risk of data leakage and misuse by unauthorized parties. Therefore, information security techniques are needed that not only protect the content of messages but also conceal the existence of the messages themselves. Steganography is an information security technique that embeds secret messages into a carrier medium without raising suspicion. Audio media is chosen because it has high tolerance for small changes in sound signals. This study discusses the implementation of the Echo Hiding steganography method for embedding secret messages in digital audio media. The Echo Hiding method works by adding an echo to the audio signal using specific delay time and amplitude parameters so that it does not significantly degrade audio quality. The research stages include audio data preparation, message embedding process, message extraction process, and evaluation of the stego audio quality. The expected results of this study show that the Echo Hiding method is capable of embedding and extracting messages accurately while maintaining audio quality. Thus, this method can be used as an alternative for audio-based steganographic information security.